Empowerment and Preservation in Mekarsari Village with the Implementation of Mingsih (Clean Week) with Youth Organization - Muhammad Al Mighwar; Alfarizzi; Choiriyatussyaadah; Naswanathania Azzahra (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This empowerment aims to analyze the impact of the implementation of the Clean Week (Mingsih) program with the Youth Organization on improving environmental sustainability in Mekarsari Village. Karang Taruna is a village youth organization that has an important role in carrying out social and environmental activities. The methodology used includes interviews with Karang Taruna members, observation of community participation in Clean Week, and analysis of social and environmental changes before and after program implementation. The results showed that the implementation of Clean Week with Karang Taruna had a positive impact on community empowerment in Mekarsari Village. The program succeeded in increasing environmental awareness, active participation of the community in cleaning the village and creating a sense of solidarity between generations. In addition, significant progress has been recorded in environmental pro tection and improved quality of life in the village. This study makes an important contribution to understanding the role of youth organizations in village development and environmental protection. The implication of this study is the need to support and develop similar programs to encourage active communityparticipation in environmental empowerment at the village level.